Cognitive screening test in primary care: cut points for low education - Yokomizo, Juliana Emy; Seeher, Katrin; Oliveira, Glaucia Martins de; Silva, Laís dos Santos Vinholi e Silva; Saran, Laura; Brodaty, Henry; Aprahamian, Ivan; Yassuda, Monica Sanches; Bottino, Cássio Machado de Campos (Revista de Saúde Pública, 2018)
OBJECTIVE: To establish the diagnostic accuracy of the Brazilian version of the General Practitioner Assessment of Cognition (GPCOG-Br) compared to the Mini-Mental State Examination (MMSE) in individuals with low educational level. METHODS: Ninety-three patients (≥ 60 years old) from Brazilian primary care units provided sociodemographic, cognitive, and functional data. Receiver operating characteristics, areas under the curve (AUC) and logistic regressions were conducted. RESULTS: Sixty-eight patients with 0–4 years of education. Cases (n = 44) were older (p = 0.006) and performed worse than controls (n = 49) on all cognitive or functional measures (p < 0.001). The GPCOG-Br demonstrated similar diagnostic accuracy to the MMSE (AUC = 0.90 and 0.91, respectively) and similar positive and negative predictive values (PPV/NPV, respectively: 0.79/0.86 for GPCOG-Br and 0.79/0.81 for MMSE). Adjusted cut-points displayed high sensitivity (all 86%) and satisfactory specificity (65%–80%). Lower educational level predicted lower cognitive performance. CONCLUSIONS: The GPCOG-Br is clinically well-suited for use in primary care.